Influence of Debris-Flow Impact on the Structural Stability of Check Dams - Eu, Song; Im, Sangjun (Frontiers in Earth Science, 2022)
Small check dams are widely used in the Republic of Korea to mitigate and prevent sediment-driven damages by mountain torrents. This study aimed to quantify the combined effects of debris-flow impact forces and earth pressures from dam sedimentations on the structural stability of a dam by incorporating the change in the longitudinal profile of the channel bed owing to sediment deposition. A debris-flow simulation model (Hyper Kanako) was used to reproduce the debris-flow behavior from the 2011 Mt. Umyeon landslide (Seoul, Republic of Korea). Finite element analysis was conducted to analyze the structural stability of the check dam under various debris discharge and sedimentation scenarios. The magnitudes of impact forces that were exerted on the check dam ranged from 81.76 kPa under a non-deposition scenario to 123.04 kPa under a 100% deposition scenario. The resultant tensile and compressive stresses were found to be up to 0.80 and 0.35 MPa, respectively, which were lower than the maximum allowable strengths of the dam, securing sufficient strength for the dam stability. Overall, the proposed approach can be applied to obtain a better understanding of the resultant internal stresses experienced during debris flow and sediment deposition, thereby providing valuable information for the structural analysis and safety assessment of check dams.